Microstructural, modal and geochemical changes as a result of granodiorite mylonitisation – a case study from the Rolovská shear zone (Čierna hora Mts, Western Carpathians, Slovakia) - Farkašovský, Roman; Bónová, Katarína; Košuth, Marián (Geologos, 2016)
Strong tectonic remobilisation and shear zone development are typical features of the easternmost part of the Veporicum tectonic unit in the Western Carpathians. The granodiorite mylonites in the area of the Rolovská shear zone (Čierna hora Mts) underwent a complex polystage evolution during the Hercynian and Alpine orogenies. Deformation during the latter reached greenschist facies under metamorphic conditions. Mylonites are macroscopically foliated rocks with a stretching lineation and shear bands. Structurally different mylonite types, ranging from protomylonites to ulramylonites with typical grainsize reduction from the margins towards the shear zone centre, have been assessed. The modal mineralogy of the different mylonite types changes considerably. Typical is a progressive decrease in feldspar content and simultaneously the quartz and white mica content increases from protomylonites towards the most strongly deformed ultramylonites. The deformation had a brittle character in less deformed rocks and a ductile one in more deformed tectonites. Obvious chemical changes occur in mesomylonites and ultramylonites. During mylonitisation, the original biotite granodiorite was depleted of Mg, Fe, Na, Ca and Ba, while K, Rb and mainly Si increased considerably. Other (major and trace) elements reflect erratic behaviour due to lateral mobility. Chemical changes indicate the breakdown and subsequent recrystallisation of biotite and feldspars and, in turn, the crystallisation of albite and sericite. REE decrease in ultramylonites due to the breakup of accessory minerals during deformation and alteration.